Contribution of travel participation to social integration and life satisfaction after spinal cord injury. Issue 4 (October 2021) - Zhao, HaoAi; Zhang, Ye; Wang, Weixuan; Cole, Shu
Abstract: Background: Research has found that participation in travel declines for people after spinal cord injury (SCI) because the traumatic injury usually results in impaired physical mobility and sensation, and barriers in the environment make travel more challenging. While travel participation can offer numerous physical, psychological, and emotional benefits, empirical evidence on positive outcomes of travel for people after SCI is scarce in the literature. Objective: To empirically examine the effects of travel participation on social integration and life satisfaction for people with SCI, along with other personal characteristics including income, self-perceived health status, levels of physical independence, occupational activities, and travel barriers. Methods: Cross sectional data are collected from 250 patients enrolled in a SCI Model System. Hierarchical regression analyses, followed by mediation analyses, are conducted to assess the effects of travel participation on social integration and life satisfaction. Results: Travel participation along with occupational activities is shown to significantly impact social integration, with participation in occupational activities partially mediating the relation from travel participation to social integration. The significant effect of travel participation on life satisfaction is fully mediated by social integration. Income and self-perceived health status both significantly contribute to social integration and life satisfaction. Conclusions: Travel participation should be considered as an independent domain that directly impacts the social integration of people with SCI, which in turn enhances their life satisfaction. Systematic interventions with standard protocols for travel-related skill training and assessments procedures are needed for people after SCI.